Childhood cancer in an incipient adult: empathetic analysis by life narrative and poetic play (Comunicação & Inovação, 2024)
Adolescence is a phase of emotional, intellectual and physical growth, in which it is not expected to become ill. Faced with cancer, this phase is interrupted, and new fears and anxieties arise, especially the fear of finitude. This article aims to present a poetic piece drawn from the life narrative of a teenager with cancer, collected in an Oncology outpatient clinic, through expanded anamnesis. The narrative reveals veiled aspects of the disease, personal and family conflicts and the difficulties and challenges in facing the life-threatening disease, being an important tool for health professionals, as well as for the teaching-learning process.
Keywords: Narrative medicine; poetic piece; palliative care